PENGARUH MEDIA KARTU TRUTH OR DARE TERHADAP HASIL BELAJAR MATEMATIKA DI KELAS IV SD NEGERI 122357 PEMATANG SIANTAR - Sitohang, Cinthya Roulina; Thesalonika, Emelda; Sijabat, Desi (SENTRI: Jurnal Riset Ilmiah, 2023)
This research aims to find out whether the use of Truth or Dare Card Media has an influence on the learning outcomes of Class IV Students at SD Negeri 122357 Pematang Siantar on fractions. This research is a type of experimental research using a quantitative approach using One Group Pretest-Posttest Design. The population of this study was all students in class IV-C of SD Negeri 122357 Pematang Siantar, totaling 25 people. Based on the results of hypothesis testing, tcount>ttable is 17,180 > 1,711 at a significance level of 0.05. This means that the hypothesis in this study can be accepted and it is stated that there is a positive and significant influence from the use of Truh Or Dare card media on the mathematics learning outcomes of fourth grade students at SD Negeru 122357 Pematang Siantar.